Effect of Segmented Sleeping on the Academic Performance of Medical Students. A Questionnaire Survey (Medico Legal Update, 2021)
Background: Sleep is a basic need of every individual, essential for a better quality of life and performancein the activity of daily living. Humans spend a third of their life sleeping. Even then, sleep disturbance isthe common health issue in modern society which promotes late-night gatherings and shift-based work.Segmented sleep is one or many naps with one core sleep where the awake period also takes place in two ormore sessions. Segmented sleep is considered to be an unhealthy practice today, is the way that our ancestorsslept until the last few centuries.Aim and Objectives: The study aims to assess the effect of segmented sleep patterns among medicalstudents and correlating it with the academic performance of them.Method and Materials: This study was done on 300 students with both male and female participants. Aquestionnaire was developed after the elaborated discussion and circulated among the students. The data wasthen analyzed using Microsoft Excel 2010.Results: The overall quality of the sleep, regardless of how long participants slept was highly satisfactory in61% and about 47% of participants spend 6–7 sleeping hours. Segmented sleeping among the participantshas a positive impact on academic performance which was both, directly and indirectly, related to the amountof time spent by the participants in their studies.Conclusion: Segmented sleep is the most natural way of treating sleep deprivation among the adolescent.Therefore, the segmented sleep pattern can be inducted in the daily schedule and then modifying to suit theindividual’s lifestyle.